2003
DOI: 10.1128/jcm.41.7.2842-2848.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Techniques forHelicobacter cetorumInfection in Wild Atlantic Bottlenose Dolphins (Tursiops truncatus)

Abstract: Helicobacter cetorum sp. nov. has been cultured from the stomach of Atlantic white-sided dolphins (Lagenorhynchus acutus) and the feces of Pacific white-sided (L. obliquidens) and Atlantic bottlenose (Tursiops truncatus) dolphins and a beluga whale (Delphinapterus leucas). H. cetorum has high homology to Helicobacter pylori as shown by 16S rRNA sequencing, and H. cetorum infection has been associated with gastritis and clinical signs in cetaceans. Because the prevalence of H. cetorum in wild populations is unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…However, the serology and histologic identification are not fast and reliable enough [29][30][31][32][33].The PCR-based molecular diagnostic techniques have been used for testing H. Pylori infections for about a decade [34,35]. Our meta-analysis revealed some concerns using the available evidences, which basically reflects the experience with PCR-based molecular diagnosis of H. Pylori infection among patient with OME, including the limitation of available evidences and a considerable variability among the available studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the serology and histologic identification are not fast and reliable enough [29][30][31][32][33].The PCR-based molecular diagnostic techniques have been used for testing H. Pylori infections for about a decade [34,35]. Our meta-analysis revealed some concerns using the available evidences, which basically reflects the experience with PCR-based molecular diagnosis of H. Pylori infection among patient with OME, including the limitation of available evidences and a considerable variability among the available studies.…”
Section: Discussionmentioning
confidence: 99%
“…to infect a broad range of terrestrial hosts (Solnick & Schauer 2001), it is surprising that H. cetorum was detected in seals housed in facilities (namely AQWA and UWW) devoid of either dolphins or whales. Therefore, providing that the occurrence of such organisms was not a factor of captivity, it would seem plausible that alternative modes of transmission to the horizontal pathway proposed by Harper et al (2003a) may also be important in the dissemination of Helicobacter species amongst the marine host.…”
Section: Discussionmentioning
confidence: 99%
“…Species different to those previously characterized from terrestrial mammals have also been reported from the stomach and feces of marine mammals including dolphins, whales, harp seals and sea otters (Harper et al 2002(Harper et al , 2003a. Whilst many Helicobacter spp.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations